Hubungan Resiliensi Matematis Terhadap Kemampuan Berpikir Kritis Siswa Pada Pembelajaran Matematika - Fitri Annisa Pujiyanti; Agung Prasetyo Abadi (Journal on Education, 2023)
The rapid development of the times and the progress of science requires education to create the nation's children who are able to think critically, creatively and innovatively. One branch of education that plays a role in advancing students' critical thinking skills is mathematics. However, students often feel anxious and insecure when facing mathematical difficulties because their critical thinking skills are not trained. To deal with the anxiety that exists in students, a mathematical resilience trait is needed. Therefore, this research is to show the relationship between mathematical resilience and students' mathematical critical thinking abilities. The research method in this study uses a quantitative approach with a correlational type. The subjects of this study were class VIII students of junior high school, with the measuring tools used, namely essay tests and questionnaires, and analyzed with the help of SPSS 25 software. Based on the research results, the correlation coefficient value was 0.596, so that Ha was accepted. This means that there is a significant relationship between mathematical resilience on students' mathematical critical thinking ability.